Computational analysis of the effect of cardiac motion on left main coronary artery hemodynamics - Laila Fadhillah, Ulta Delestri; Foo, Ngai Kok; Al Abed, Amr; Dokos, Socrates; Mohd Jamil, Mohamed Mokhtarudin; Bressloff, Neil W.; Azam, Ahmad Bakir (IEEE Computer Society, 2022)
Cardiac muscle health is dependent on the ample supply of oxygenated blood to ensure optimal cardiac function. The continuous supply of oxygenated blood occurs through coronary arteries embedded within the muscle. Cardiac motions involve contracting and expanding giving rise to the biomechanical behavior of the arteries. This work studies the impact of cardiac motion on the coronary flow using a two-way fluid-structure interaction. Blood flow was modelled within an idealized 3D coronary arterial structure using incompressible laminar Navier-Stokes equations. The vessel walls of left main artery were represented using an isotropic five-parameter MooneyRivlin hyperelastic material which deformed dynamically with prescribed displacement boundary conditions to simulate ventricular torsional and expansion motions. Our results showed higher blood velocities at the bifurcation region in the moving artery than in the non-moving case, particularly during systolic torsional motion. During systole, the wall shear stress near the bifurcation was found to be lower in the non-moving case relative to the moving one. In the non-moving model, a helical-shaped pattern of secondary flow was observed as the blood flowed through the curved vessel, however this pattern diminished in the moving model, where the arterial curvature dynamically changed throughout cardiac cycle.